Benefit-Cost Analysis of the National Animal Identification System - NAIS Benefit-Cost Research Team (My University, 2010)
The purpose of this study was to conduct a benefit‐cost analysis of the United States National Animal Identification System (NAIS). The NAIS is a voluntary federal animal identification system operated by the Animal and Plant Health Inspection Service (APHIS) of the United States Department of Agriculture (USDA). NAIS is designed primarily to protect the health of the nation’s livestock and poultry to enhance animal health and maintain market access. The three components of NAIS are: 1) premises registration, 2) animal identification, and 3) animal movement tracking. Objectives of this study included estimating benefits and costs of adopting NAIS by the livestock and poultry industries as well as determining how net benefits are likely to be allocated among industry sectors, consumers, and government. The benefit‐cost analysis focuses on impacts of NAIS adoption in the bovine, porcine, ovine, poultry, and equine industries.